2012
DOI: 10.1002/ibd.21866
|View full text |Cite
|
Sign up to set email alerts
|

Role of the microbiota in inflammatory bowel diseases

Abstract: Studying the role of the human microbiome as it relates to human health status has revolutionized our view of microbial community contributions to a large number of diseases, particularly chronic inflammatory disorders. The lower gastrointestinal (GI) tract houses trillions of microbial cells representing a large diversity of species in relatively well-defined phylogenetic ratios that are associated with maintenance of key aspects of host physiology and immune homeostasis. It is not surprising, therefore, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
188
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(209 citation statements)
references
References 139 publications
15
188
0
6
Order By: Relevance
“…Previous studies have shown that the gut microbial community of IBD patients is characterized by reduced diversity and decreased abundance of the phylum Firmicutes, and a concomitant increase in the phylum Proteobacteria [6,7,31]. Several studies have found that the reduced diversity of the gut microbiota in IBD patients is primarily associated with the lower abundance of the phylum Firmicutes, particularly in the Clostridium cluster IV of anaerobic bacteria [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the gut microbial community of IBD patients is characterized by reduced diversity and decreased abundance of the phylum Firmicutes, and a concomitant increase in the phylum Proteobacteria [6,7,31]. Several studies have found that the reduced diversity of the gut microbiota in IBD patients is primarily associated with the lower abundance of the phylum Firmicutes, particularly in the Clostridium cluster IV of anaerobic bacteria [4].…”
Section: Discussionmentioning
confidence: 99%
“…The dysbiosis of IBD is characterized by a decrease in bacterial diversity and a decrease in members of the phylum Firmicutes, and concomitant expansion of the phylum Proteobacteria [6][7][8]. A reduced abundance of certain Clostridium subsets, such as cluster IV and subcluster XIVa, contributes to the decreased abundance of the phylum Firmicutes [9,10], and an increase in the phylum Proteobacteria is represented by the expansion of Enterobacteriaceae, including E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Clone libraries were constructed as described previously (15,16). Whole DNA isolated from the murine cecum was amplified with Illustra PuRe Taq ReadyTo Go PCR beads (GE Healthcare, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…La disbiosis o cambio en la microbiota juega un rol fundamental en la patogĂ©nesis de numerosas enfermedades, tanto intestinales (enfermedad inflamatoria intestinal (EII), sĂ­ndrome intestino irritable y diarrea por CD) como no intestinales, como las enfermedades metabĂłlicas [9][10][11][12] . Varios estudios han demostrado que la marcada normalizaciĂłn de la microbiota por transferencia directa de Ă©sta desde un donante sano, procedimiento conocido como TMF, es altamente efectivo en el tratamiento de CD refractario y recurrente, con un Ă©xito mayor a 90%…”
Section: Discussionunclassified